DNA-based characterization of rays (Elasmobranchii: Batoidea) from Bangladesh using mitochondrial markers: Implications for conservation and management - Mysha Mahjabin; Sujan Kumar Datta; Ahmed Farhan Labib; Sanjida Akhter; Durjoy Raha Antu; Md. Sagir Ahmed (PLoS ONE, 2026)
Rays are an iconic group of chondrichthyan fishes, with many species currently threatened with extinction. Although conservation laws exist in Bangladesh to protect their population, lack of comprehensive law enforcement strategies together with commercial exploitation and habitat destruction resulted in population decline of many species nonetheless. One significant challenge to this conservation effort is a rapid and authentic species identification strategy, as traditional morphological diagnosis is hindered by frequent misidentification, especially when species are morphologically similar or when specimens are damaged or missing key features. The emergence of DNA barcoding technique can overcome this barrier, requiring only a small tissue sample for authentic identification. In the present study, this state-of-the-art technique has been employed for species identification of rays using three different mitochondrial marker gene, namely 16s rRNA, COI, and NADH2. A total of 94 new barcode sequences were generated, including 43 COI, 31 16S rRNA, and 20 NADH2 sequences, representing 23 ray species across 15 genera, 9 families, and 3 orders. Mean genetic distances varied across markers: for COI, 0.23 within species, 7.60 within genera, and 17.34 within families; for 16S rRNA, 0.04, 5.49, and 8.72, respectively; and for NADH2, 0.22, 13.52, and 20.72, respectively. Based on genetic divergence, barcode gap, and phylogenetic resolution, NADH2 proved to be a valuable alternative marker to COI for species-level identification. In contrast, 16s rRNA displayed the lowest divergence limiting its discriminatory power for species-level identification. Approximately 82.61% of our recorded species are categorized as different threatened categories (CR, EN, VU, NT) under the IUCN Global Red List. However, only 4 species are listed in CITES Appendix II for protection, leaving the majority of the ray species vulnerable for exploitation. Furthermore, several Schedule I and II species under Bangladesh Wildlife Act are openly traded in domestic market despite their supposed protection. This study highlights the urgent need to raise awareness among fishing communities and to strengthen measures against this illegal trade of ray species listed under national wildlife protection schedules.